Confidence Games - Tanina Rostain, Milton C. Regan Jr (The MIT Press, 2014)
In late 1999, an unmarked manila envelope arrived at the U.S. Department of the Treasury.1 The appearance of a mysterious envelope at the Treasury was not uncommon at that time. Every once in a while, Treasury officials would receive a parcel containing the prospectus for a complicated tax evasion strategy. They assumed that the documents came from tax professionals who had been shown the materials by a client or had come across them at work. These professionals, worried that the Internal Revenue Service might never discover the tax ploy, wanted to alert the agency so that it could close down the strategy and prevent the loss of millions of dollars in tax revenue. Torn between their concern that the tax shelter would allow wealthy individuals improperly to avoid millions of dollars in taxes and their obligation to protect client or employer confidences, some professionals chose to try to protect the federal fisc. Anonymity was the fig leaf that allowed them to make peace with the fact that by sending the materials to the government they were betraying their clients’ or employers’ confidences. The manila envelope that happened to arrive at the Treasury that fall contained marketing materials describing a shelter known under the acronym BOSS, which was being promoted by Big Five accounting firm PricewaterhouseCoopers. From the look of the documents, BOSS was being offered to high-wealth individuals who wanted to avoid paying any taxes on large capital gains.2 If, as it turned out, the promotional documents described an abusive shelter—one whose claimed tax benefits were not recognized by the law—Treasury officials would be able to use the detailed description as a roadmap to shut down the shelter and find the taxpayers who were claiming tax benefits from the strategy. Government officials immediately began analyzing the documents and sharing them with other government agencies.